The Object Orientation Effect in Exocentric Distances - Weller, Marlene; Takahashi, Kohske; Watanabe, Katsumi; Bülthoff, Heinrich H.; Meilinger, Tobias (Frontiers in Psychology, 2018)
The object orientation effect describes shorter perceived distances to the front than to the back of oriented objects. The present work extends previous studies in showing that the object orientation effect occurs not only for egocentric distances between an observer and an object, but also for exocentric distances, that are between two oriented objects. Participants watched animated virtual humans (avatars) which were either facing each other or looking away, and afterward adjusted a bar to estimate the perceived length. In two experiments, participants judged avatars facing each other as closer than avatars facing away from each other. As the judged distance was between two objects and did not involve the observer, results rule out an explanation that observers perceive object fronts as closer to prepare for future interaction with them. The second experiment tested an explanation by predictive coding, this is the extrapolation of the current state of affairs to likely future states here that avatars move forward. We used avatars standing on bridges either connecting them or running orthogonal to the inter-avatar line thus preventing forward movement. This variation of walkability did not influence participants’ judgments. We conclude that if predictive coding was used by participants, they did not consider the whole scene layout for prediction, but concentrated on avatars. Another potential explanation of the effect assumes a general asymmetrical distribution of inter-person distances: people facing each other might typically be closer to each other than when facing away and that this asymmetry is reflected as a bias in perception.